Displaying Mobile Feedback During a Presentation - Teevan, Jaime; Liebling, Dan; Paradiso, Ann; Garcia Jurado Suarez, Carlos; von Veh, Curtis; Gehring, Darren (Proc. MobileHCI 2012, 2012)
Smartphone use in presentations is often seen as distracting to the audience and speaker. However, phones can encourage people participate more fully in what is going on around them and build stronger ties with their companions. In this paper, we describe a smartphone interface designed to help audience members engage fully in a presentation by providing real time mobile feedback. This feedback is then aggregated and reflected back to the group via a projected visualization, with notifications provided to the presenter and the audience on interesting feedback events. We deployed this system in a large enterprise meeting, and collected information about the attendees’ experiences with it via surveys and interaction logs. We find that providing mobile phone-based feedback is convenient, helps attendees pay close attention to the presentation, and enables them to feel connected with other audience members.